RNA Biomarkers: Glycan Stimulation Enables Purification of Prostate Cancer Circulating Tumor Cells on PEDOT NanoVelcro Chips for RNA Biomarker Detection (Adv. Healthcare Mater. 3/2018). Issue 3 (7th February 2018) - Shen, Mo‐Yuan; Chen, Jie‐Fu; Luo, Chun‐Hao; Lee, Sangjun; Li, Cheng‐Hsuan; Yang, Yung‐Ling; Tsai, Yu‐Han; Ho, Bo‐Cheng; Bao, Li‐Rong; Lee, Tien‐Jung; Jan, Yu Jen; Zhu, Ya‐Zhen; et al.
Abstract : In article number1700701, Hsiao‐hua Yu and co‐workers purified circulating tumor cells (CTCs) from blood samples of prostate cancer (PCa) patients. This platform not only captures CTCs with high efficiency and specificity, but also, released these cells gently by a competitive‐binding mechanism. The purified CTCs provide well‐preserved RNA transcripts for the analysis of the expression level of several PCa‐specific RNA biomarkers, which could provide clinical insights into the disease and valuable information for cancer diagnosis and therapeutics.